The Relationship oF Learning Motivation with Student Satisfaction with the Learning Process of Laboratory Practices in the COVID-19 Pandemic Era - Nilakesuma, Nur Fadjri; Susilawati, Dewi (Jurnal Midpro, 2022)
Online learning is considered to be the best solution for teaching and learning activities during the COVID-19 pandemic. Mercubaktijaya Padang STIKes as a means and educational institution must be able to adapt to facilitating all adjustments concerning the student education system during the COVID-19 pandemic, including modifying learning methods, both theoretical learning and laboratory practical learning. The difficulties experienced by students when practicing online laboratories will have an impact on decreasing student learning motivation. The low motivation to learn will affect the results of the learning process, therefore, the problem of learning motivation needs special attention. Objective: to determine the relationship between student learning motivation and satisfaction with online laboratory practices in the Midwifery Undergraduate Education Study Program and the Midwife Professional Study Program, Mercubaktijaya STIKes Profession Program, Padang. Methods: descriptive-analytic with a cross-sectional design. The research sample was 2nd level students of the Undergraduate Midwifery Study Program and the Midwife Profession Study Program Mercubaktijaya Padang STIKes Profession Program with the instrument used was survey data. Data collection was carried out using a google form which was held from September 22 – to October 30, 2021. This research was analyzed by chi-square test using Microsoft excel application (X2 tabel : 3, 841) Results: . The results of the study showed that there was a relationship between student learning motivation and the online laboratory practice learning process (X2 hitung sebesar 5,685), the competence of supervisors (X2 hitung sebesar 7,272), and infrastructure during online laboratory practice (X2 hitung sebesar 6,012), Conclusions and Suggestions: showed that there was a relationship between student learning motivation and the online laboratory practice learning process, the competence of supervisors, and infrastructure during online laboratory practice. Need to increase student motivation to increase student satisfaction with the learning process, lecturer competence, and infrastructure.